'Use of stories that aren't even true': reading Salman Rushdie's Haroun and the Sea of Stories and Luka and the Fire of Life. Issue 5 (4th May 2021) - Mujral, Rajni
ABSTRACT: This paper argues that the act of storytelling is inventive and performative. Tracing the idea of truth and lie as discursive enactments, the paper discusses that stories cannot be stipulated by the binary of truth and lie. It is a discursive repetition that invents and produces the truth of fiction. The truth of fiction has to be mediated by the reality that it establishes for itself in the process of its creation. This proposition is developed further in this paper to understand how the mode of tell-tale institutes the phantasm or fictionality. This is examined while keeping Salman Rushdie's novellas in the background. The larger frame of the paper comes from the statement Salman Rushdie makes in Luka and the Fire of Life (2010). He defines the human as a storytelling animal and says that the identity and meaning of life are in stories. This force of the narrative that gives meaning to life enabled Rushdie to take up Haroun and the Sea of Stories (1990) under the fatwa. The narrative is also about the power of literature as an institution. Moreover, both the novellas become parables of the power of the literary.